INDENTIFIKASI HIGH PERFORMANCE WORK SYSTEM - I Nengah Aristana; I Wayan Arta Artana (Badung: LPPM Universitas Triatma Mulya, 2020)
The development of the business world now requires all forms of business including cooperatives to do various ways to increase productivity and performance. One of the efforts in increasing productivity and performance is by building a high-performance work system. The purpose of this research is to find out the high performance work system in cooperatives. The number of respondents was 132 respondents with factor analysis analysis techniques. From the results of the analysis conducted found three factors as determinants of high performance work systems, namely the method of task delegation, internal planning and motivation.